Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan Pada Perusahaan BUMN Sektor Konstruksi Tahun 2017-2022 - Faizal Rahmad; Dudi Rudianto (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the relationship between corporate governance, solvency and Corporate Social Responsibility (CSR) variables with the financial performance of State-Owned Enterprises (BUMN) in the construction sector for the period 2017 to 2022. This research method uses secondary research data from company annual reports with research sample of 4 state-owned companies in the construction sector. Secondary data sources were taken from the annual reports of the companies that were the research sample. Data analysis uses the Chow, Hausman Test with the help of the E-views application. The results of this research provide important information for company management in improving financial performance and asset management strategies in BUMN in the construction sector. So it can be concluded as follows: (1) There is a negative and significant influence of corporate governance as measured by community ownership (KM) on the measured financial performance with return on assets (ROA), (2) There is a positive and significant influence of corporate governance as measured by institutional ownership (KI) on financial performance as measured by return on assets (ROA), (3) There is a positive and significant influence on solvency as measured with debt to equity ratio (DER) on financial performance as measured by return on assets (ROA), (4) There is a negative and significant influence of solvency as measured by debt to asset ratio (DAR) on financial performance as measured by return on assets ( ROA), (5) There is no influence of Corporate Social Responsibility as measured by the global reporting initiative (GRI) on financial performance as measured by return on assets (ROA), (6) Corporate governance mechanisms, solvency and corporate social responsibility have a significant effect simultaneously on the financial performance of BUMN in the Construction Sector.